An Analytical Survey on the Solutions of the Generalized Double-Order φ-Integrodifferential Equation. (12th February 2021) - Rezapour, Sh.; Ntouyas, S. K.; Iqbal, M. Q.; Hussain, A.; Etemad, S.; Tariboon, J.
Abstract : We study the existence of solutions for a newly configured model of a double-order integrodifferential equation including φ -Caputo double-order φ -integral boundary conditions. In this way, we use the Krasnoselskii and Leray-Schauder fixed point results. Also, we invoke the Banach contraction principle to confirm the uniqueness of the existing solutions. Finally, we provide three examples to illustrate our analytical findings.